Differential effects of hydrocortisone, prednisone, and dexamethasone on hormonal and pharmacokinetic profiles: a pilot study in children with congenital adrenal hyperplasia. (December 2016) - Nebesio, Todd; Renbarger, Jamie; Nabhan, Zeina; Ross, Sydney; Slaven, James; Li, Lang; Walvoord, Emily; Eugster, Erica
Abstract Background Little is known about the comparative effects of different glucocorticoids on the adrenal and growth hormone (GH) axes in children with congenital adrenal hyperplasia (CAH). We sought to compare the effects of hydrocortisone (HC), prednisone (PDN), and dexamethasone (DEX) in children with classic CAH and to investigate a potential role of pharmacogenetics. Methods Subjects were randomly assigned to three sequential 6-week courses of HC, PDN, and DEX, each followed by evaluation of adrenal hormones, IGF-1, GH, and body mass index (BMI). Single nucleotide polymorphism (SNP) analysis of genes in the glucocorticoid pathway was also performed. Results Nine prepubertal subjects aged 8.1 ± 2.3 years completed the study. Mean ACTH, androstenedione, and 17-hydroxyprogesterone (17-OHP) values were lower following the DEX arm of the study than after subjects received HC (p ≤ 0.016) or PDN (p ≤ 0.002). 17-OHP was also lower after HC than PDN (p < 0.001). There was no difference in IGF-1, GH, or change in BMI. SNP analysis revealed significant associations between hormone concentrations, pharmacokinetic parameters, and variants in several glucocorticoid pathway genes (ABCB1, NR3C1, IP013, GLCCI1 ). Conclusions DEX resulted in marked adrenal suppression suggesting that its potency relative to hydrocortisone and prednisone was underestimated. SNPs conferred significant differences in responses between subjects. Although preliminary, these pilot data suggest that incorporating pharmacogenetics has the potential to eventually lead to targeted therapy in children with CAH.